PERANCANGAN MEKANISME MOTOR STIRLING BERKAPASITAS 1 kW - Hardianto, Toto; Suharto, Djoko; Dirgantara, Tatacipta (Mesin, 2001)
The Stirling engine is an external combustion engine for converting the thermal energy into mechanical energy. This engine uses a Stirling cycle, which theoretically could have high thermal efficiency, which is as high as a Carnot cycle operating at a similar condition.This paper deals with a design process of Stirling engineâs mechanism stressing on the kinematics and dynamics aspects. Thermodynamics and geometry parameters are the inputs required for designing the Stirling engineâs mechanism. Material aspect has not been included in the design. The main parameters analyzed are: engineâs rotational speed, working temperature, cylinderâs pressure, inertial forces and power output.The results of the design are useful to give an overall picture of the main dimensions of a Stirling engine. Detail calculations are still needed for more advanced design.